Polemics on Interfaith Marriage: Law and Civil Law Perspectives - Muhammad Habiby Abil Fida Safarin; Fatimah Fatimah (Universitas Kuningan, 2021)
Marriage is seen as a bridge to a long journey that has shared visions and missions. We can not recklessly hold a wedding. There are a few things to be considered. Umumnya adalah budaya dan agama yang menjadi sorot utama ketika pemuda pemudi atau calon mempelai pria dan wanita akan melangsungkan pernikahan. Budaya merupakan hal yang juga akan dibawa ketika acara pernikahan akan dilangsungkan. Generally, culture and religion become the highlight once man and woman or prospective brides and grooms plan to get married. Culture is presented on the wedding day. However, a different culture is not allowed or prohibited. This also applies to religion. It becomes an important matter to consider before marriage. Marriage must be carried out according to each partner's religion. Thus, it is considered valid. In general, marriages are held in the same religion. However, this study will discuss massive interfaith marriages done by young people in Indonesia. The study employed a literature approach. This approach requires more reading and collecting library data. The findings generated new ideas in civil matters, the registration of interfaith marriages and the challenges of holding such marriage. In conclusion, interfaith marriages bring countless problems if they insist.